Tomato powder supplementation activates Nrf-2 via ERK/Akt signaling pathway and attenuates heat stress-related responses in quails - Şahin, Kazım; Orhan, C.; Akdemir, F.; Tuzcu, M.; Ali, S.; Şahin, Nurhan. (Elsevier, 2011)
Rearing birds at temperatures higher than thermoneutral temperature might impair cellular signal transduction pathways, influencing the expression of genes coding for antioxidant proteins, and affect the laying performance of the bird. This experiment was conducted to evaluate the effects of tomato powder supplementation on the activation of nuclear factor erythroid 2-related factor 2 (Nrf-2), and phosphorylated forms of extracellular signal-regulated kinase (ERK) 1/2 and protein kinase B (Akt) in heat stressed Japanese quails (Coturnix coturnix Japonica). A total 01 180 five-week-old female Japanese quails were reared either at 22 degrees C for 24 h/d (thermoneutral, TN) or 34 degrees C for 8 h/d (heat stress, HS) for 12 weeks. Birds were randomly fed one of the three diets: basal diet or basal diet supplemented with 25 or 50 g/kg tomato powder. Each of the 2 x 3 factorially arranged groups was replicated in 10 cages, each containing 3 quails. Significantly higher level of Nrf-2 (P<0.001), ERK 1/2 (P<0.001) and Akt (P<0.001) were found in HS quails when compared to the TN group. The effect was dose dependent, and counteracted by tomato powder supplementation. The HS group also showed a concomitant increase in the activation of nuclear factor-kappa B (NF kappa B), a transcription factor regulating the expression of genes involved in inflammation (P<0.001). The activation of NF kappa B decreased close dependently in HS quail supplemented with tomato powder. The level of hepatic peroxide and superoxide decomposing enzymes measured in tomato powder supplemented group of HS birds also increased (P<0.001). In conclusion, tomato powder is likely to augment cellular antioxidant defense in HS quails by causing an increase in the level of phosphorylated forms of Akt and ERK, leading to the activation of Nrf-2, and reduce inflammation by inhibiting NF-kappa B. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Lycopene; Transcription factors; Heat stress; Quail